Hospedar el fenómeno : hacia una ética de la fenomenalidad en Jean-Luc Marion - Murga, Ezequiel Daniel (Sapientia, 2019)
The contemporary phenomenology has rethought the place of subjectivity starting from receptivity, whether it is from the self, the other, the event or the phenomena in general. Whithin this context, Marion’s work proposes a reception of the phenomena from their giveness. Given that the phenomena take the initiative that is given by its own self, the subject is left in the position of receptivity, by receiving what it is given and being responsible for the modes of phenominalization. In this paper, we propose to dive deep into the dimension of the subject’s responsibility whitin Marion’s work when it comes to receiving, hosting and phenominalising what’s given.